2004
DOI: 10.1007/s00421-004-1052-2
|View full text |Cite
|
Sign up to set email alerts
|

The upper limit of physiological cardiac hypertrophy in elite male and female athletes: the British experience

Abstract: Establishment of upper normal limits of physiological hypertrophy in response to physical training is important in the differentiation of physiological and pathological left ventricular hypertrophy. The genetic differences that exist in the adaptive response of the heart to physical training and the causes of sudden cardiac death in young athletes indicate the need for population-specific normal values. Between September 1994 and December 2001, 442 (306 male, 136 female) elite British athletes from 13 sports w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
79
1
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(90 citation statements)
references
References 18 publications
6
79
1
4
Order By: Relevance
“…While our and previous studies agree on normal systolic function (15,17), previous studies have been conflicting with regard to diastolic function in athletes. Doppler-echocardiography and tissue Doppler imaging studies have shown either normal (12,17,(31)(32)(33)(34)(35) or augmented diastolic function (36 -39). A disadvantage of some of the previous studies is the lack of age-and sex-matched groups of sedentary controls (31,36,38).…”
Section: Discussionmentioning
confidence: 99%
“…While our and previous studies agree on normal systolic function (15,17), previous studies have been conflicting with regard to diastolic function in athletes. Doppler-echocardiography and tissue Doppler imaging studies have shown either normal (12,17,(31)(32)(33)(34)(35) or augmented diastolic function (36 -39). A disadvantage of some of the previous studies is the lack of age-and sex-matched groups of sedentary controls (31,36,38).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] Part of the controversy may be related to the fact that only few studies took into account body composition when scaling cardiac dimensions. In this study, we sought to determine, in college athletes, whether sex-related differences in ventricular dimensions persisted after adjustment for lean body mass (LBM).…”
Section: Introductionmentioning
confidence: 99%
“…The enlargement of the heart chambers, increase of the end-diastolic interventricular septal thickness (IVSTd), enddiastolic posterior wall thickness (PWTd), and maintenance of the IVSTd/PWTd ratio document physiological cardiac hypertrophy as a consequence of training. [1][2][3][4][5] One of the distinct features of physiological adaptations versus pathological adaptations in heart morphology is the tendency to return toward baseline values with cessation of or decrease in training, although the process of adaptation to training is more obvious than adaptation to detraining. 6 The increase in heart dimensions (expressed as the increase in the size of the left ventricular internal diameter at end diastole [LVIDd]) and hypertrophy (expressed as the increase in the PWTd) are adaptations to high-load training.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] The pathological threshold of these adaptations has been established as 60 mm for LVIDd. 3,5,10,11 The cardiac adaptations to different types of training are still not defined clearly. 6,[12][13][14] We performed a longitudinal echocardiographic study of nationally and internationally ranked runners over 5 seasons to determine intense training-induced heart adaptations in elite endurance runners and elite sprinters.…”
Section: Introductionmentioning
confidence: 99%